Analyzing students’ errors in solving HOTS mathematics problems based on Newman theory - Melania, Tika Eri; Nurnugroho, Burhanudin Arif (Universitas Ahmad Dahlan, 2023)
This research is motivated by the existence of the 2013 curriculum, students are required to have the ability to solve problems independently. In supporting this, the strategy in the 2013 curriculum is learning to apply HOTS type questions. This is also applied in the Muhammadiyah Boarding School Pleret. However, when students worked on HOTS questions, it was seen that students still made many mistakes in working on HOTS questions. This study aims to: (1) Know the types of errors made by students of class XI MBS Pleret in solving Higher Order Thinking Skills (HOTS) Mathematics questions based on Newman's error analysis (2) Know the factors that cause errors in class XI MBS Pleret students in solving problems Higher Order Thinking Skills (HOTS) Mathematics. This type of research is descriptive qualitative. The subjects of this study were students of class XI MBS Pleret, while the object of this research was HOTS (High Order Thinking Skill) type questions. Data collection methods are conducting tests and interviews with students. The instruments used in this study were test questions, interviews and documentation. The analytical method used in this study is data reduction, data presentation, and drawing conclusions. The results of this study were (1) Types of errors made by students of class XI MBS Pleret in solving HOTS questions on trigonometry equation material based on Newman's error analysis consisting of reading errors, understanding errors, transformation errors, skills errors, and errors in writing the final answer. Based on the student error percentage table, the most students made mistakes in the process skills of 98.8% and the errors in writing the final answer was 98.8%. Then for the transformation error of 90.4%, the error in understanding is 67.3% and the smallest error is a reading error which is 66.67%. (2) The causal factors are that students do not know the α symbol (reading errors), students are not used to writing and are known and asked questions other than story questions (comprehension errors), students forget the formula to work on HOTS questions (transformation errors), the result of previous mistakes students made process skill errors and mistakes in writing the final answer.